The Influence of Utilitarian Value on Repurchase Intention through Attitude among Bandung Indah Plaza Visitors - Vira Novita; Edi Nurtjahjadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study explores whether utilitarian value contributes to repurchase intention by considering attitude as an intervening variable among visitors to Bandung Indah Plaza. The research employed a cross-sectional quantitative design with 126 Generation Z participants from the Greater Bandung area recruited using purposive sampling. Data were collected through an online questionnaire and processed using descriptive analysis, simple and multiple linear regression techniques, together with Sobel mediation analysis in SPSS version 27. The empirical results reveal a statistically significant positive relationship between utilitarian value, attitude, and repurchase intention. Moreover, attitude significantly promotes repurchase intention while simultaneously functioning as the mechanism through which utilitarian value influences repurchase intention. Overall, the findings suggest that shopping center management should emphasize functional shopping experiences, including convenience and efficiency, to encourage repeat purchasing behavior in offline retail environments.